2020
DOI: 10.1093/tas/txaa142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid profile of supplements on intake, performance, carcass traits, meat characteristics, and meat sensorial analysis of feedlot Bos indicus bulls offered a high-concentrate diet

Abstract: This experiment was designed to evaluate the effects of lipid source and fatty acid (FA) profile on intake, performance, carcass characteristics, expression of enzymes, and sensorial analysis of B. indicus animals offered a high-concentrate diet. On day 0, 96 non-castrated animals were blocked by initial body weight (400 ± 19.3 kg), randomly allocated to 1 of 24 pens (4 animals/pen), and pens were randomly assigned to receive: 1) Control: basal diet composed of whole cottonseed and corn germ as lipid substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
(88 reference statements)
2
9
2
Order By: Relevance
“…In fact, in a traditional feedlot production setting, subcutaneous depots are stored and formed prior to intramuscular fat depots (i.e., marbling; Vernon, 1981 ; Sainz and Hasting, 2000 ; Oliveira et al, 2011 ) and, therefore, it can be speculated that intramuscular fat depot differentiation would still occur in non-castrated Bos taurus indicus animals as they would achieve mature BW ( Valadares Filho et al, 2016 ). Likewise, Costa et al (2020) reported similar marbling scores in non-castrated Bos taurus indicus animals slaughtered at similar BW and offered high-concentrate diets with similar ether extract contents as used herein. This lack of marbling might change when starch is offered to beef cattle early in life, resulting in epigenetic effects ( Reis et al, 2015 ) that will improve marbling scores later in life ( Scheffler et al, 2014 ).…”
Section: Discussionsupporting
confidence: 61%
“…In fact, in a traditional feedlot production setting, subcutaneous depots are stored and formed prior to intramuscular fat depots (i.e., marbling; Vernon, 1981 ; Sainz and Hasting, 2000 ; Oliveira et al, 2011 ) and, therefore, it can be speculated that intramuscular fat depot differentiation would still occur in non-castrated Bos taurus indicus animals as they would achieve mature BW ( Valadares Filho et al, 2016 ). Likewise, Costa et al (2020) reported similar marbling scores in non-castrated Bos taurus indicus animals slaughtered at similar BW and offered high-concentrate diets with similar ether extract contents as used herein. This lack of marbling might change when starch is offered to beef cattle early in life, resulting in epigenetic effects ( Reis et al, 2015 ) that will improve marbling scores later in life ( Scheffler et al, 2014 ).…”
Section: Discussionsupporting
confidence: 61%
“…This experimental design allowed the direct comparison of how the inclusion of these lipid feedstuffs (WC and CSFA) would impact performance and carcass traits of feedlot B. indicus beef cattle. It is noteworthy mentioning that one might question the lack of an experimental group containing only WC as the sole lipid source, but the explanation for this includes 1) possible negative effects of a greater dietary WC inclusion (>15% DM) on performance and carcass traits have been reported by others ( Zinn, 1996 ; Cranston et al, 2006 ; Gouvêa et al, 2020 ), 2) the WC levels used herein are representative of the current nutritional practices in Brazilian feedlots ( Pinto and Millen, 2019 ), and 3) to the best of our knowledge, no other research evaluated different levels of both lipid sources in the same experiment ( Carvalho et al, 2020 ; Costa et al, 2020 ), and further studies are warranted.…”
Section: Discussionmentioning
confidence: 88%
“…Dressing percent (DP) was calculated by dividing the HCW by final shrunk BW of the animal on day 108 of the experiment. Per standard industry procedures, initial DP of the animals was estimated at 50% ( Costa et al, 2020 ) and then it was calculated the amount of carcass gained by the animals during the experimental period (day 0 to 108). Carcass ADG was calculated by dividing the carcass gain and the number of days on feed (108 d), whereas yield gain (YG) was calculated by dividing carcass ADG (in kg) and ADG (in kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, whereas certain management practices such as grazing or free range may be preferred by consumers over confined feeding particularly from an animal welfare lens, some aspects of feeding and management are of interest due to their impacts on product quality. For instance, compounds that affect flavor of meat and eggs, including fatty acids, some nutraceutical compounds, and other feed additives (e.g., Guo et al, 2019;Mwangi et al, 2019;Costa et al, 2020;Feng et al, 2020;Yu et al, 2020) are of considerable interest when responses can be confirmed in a production setting. However, the mechanisms of action of these compounds need to be well-described and verified.…”
mentioning
confidence: 99%